2020
DOI: 10.1177/0890117120934609
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Races in Health Information Seeking and Trust Over Time: Evidence From a Cross-Sectional, Pooled Analyses of HINTS Data

Abstract: Purpose: Assessed racial disparities in health information-seeking behavior and trust of information sources from 2007 to 2017. Design: Pooled cross-sectional survey data. Setting: Health Information National Trends Survey (HINTS). Participation: Data included 6 iterations of HINTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…In national surveys that used items asking respondents how much they trusted information from a doctor, levels of trust were relatively high across racial and ethnic groups with a few exceptions. Hispanic men reported lower levels of trust in information from their doctor compared to White and Black men, and this difference appears to be stable across multiple waves of the HINTS [48] . Black women reported higher levels of trust in other sources such as government health agencies, television, religious organizations, and family members compared to White women, and this finding also remained consistent over time [48] .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In national surveys that used items asking respondents how much they trusted information from a doctor, levels of trust were relatively high across racial and ethnic groups with a few exceptions. Hispanic men reported lower levels of trust in information from their doctor compared to White and Black men, and this difference appears to be stable across multiple waves of the HINTS [48] . Black women reported higher levels of trust in other sources such as government health agencies, television, religious organizations, and family members compared to White women, and this finding also remained consistent over time [48] .…”
Section: Discussionmentioning
confidence: 88%
“…Hispanic men reported lower levels of trust in information from their doctor compared to White and Black men, and this difference appears to be stable across multiple waves of the HINTS [48] . Black women reported higher levels of trust in other sources such as government health agencies, television, religious organizations, and family members compared to White women, and this finding also remained consistent over time [48] . In contrast, studies that used the validated Group-Based Medical Mistrust Scale (GBMMS) found that Black women had the highest levels of mistrust and White women had the lowest levels [28] , and levels of mistrust were higher among unvaccinated women compared to vaccinated women.…”
Section: Discussionmentioning
confidence: 88%
“…Previous research has indicated that these platforms as a source of support for cancer may be too general and more emotionally oriented (as opposed to focused on resources/needs) [33]. Popular social media outlets such as Facebook may also provide information that needs to be appraised for quality to ensure that it is evidence based [34,35]. Recent developments in online support group platforms include patient-generated health-data cohorts, where cancer survivors can report health data and experiences through their mobile and wearable health devices [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research does not provide enough clarity on how these factors might affect internet-based information-seeking behaviors of African American and Hispanic men with chronic conditions; however, there is reason to expect some differences. Some studies have examined web-based health information seeking by race [ 29 , 30 ] or by sex, specifically for men with chronic diseases [ 31 ], but did not focus specifically on African American and Hispanic men with chronic conditions. This population has been found to experience important barriers to disease self-management [ 32 ], have less access to health insurance and preventative care [ 33 ], have higher rates of preventable hospitalizations [ 34 ], and are more likely to die from their chronic conditions compared with non-Hispanic White men [ 35 ].…”
Section: Introductionmentioning
confidence: 99%